(untitled) (Swiss Medical Weekly, 2016)
PRINCIPLES: Neuroendocrine neoplasms (NENs) are believed to be associated with an increased risk for additional malignancies (AMs). We aimed to (1) assess the occurrence of AM in NEN patients (2) investigate the characteristics and temporal relationship of NEN patients with and without AM. METHODS: The SwissNET registry has prospectively documented patients with NEN since 2008, covering the entire area of Switzerland. Clinical characteristics, functionality, location and histology of NEN as well as survival of all consecutive patients were retrieved. The characteristics of the AM (location, histology, time point of diagnosis in relation to diagnosis of NEN) were extracted. RESULTS: Out of 934 patients, 193 patients (21%) presented with AMs. There was no statistically significant difference with regard to location, functionality and grading (G1–G3) between the NEN patients with and without AM. AMs were diagnosed synchronously (±3 months), before (>–3 months) and after (>+3 months) diagnosis of NEN in 82 (42%), 96 (50%) and 13 (7%) patients, respectively. Location of NEN correlated with the anatomical origin of the AM. Age- and gender- corrected survival was not significantly different between NEN patients with and without AM. CONCLUSION: The prevalence of AM in NEN is high. The comparable characteristics with regard to functionality and grading in the NEN cohorts with and without AM and the similar location of AM and NEN suggest a selection bias towards frequent imaging procedures in NEN patients with AM.